IMPLEMENTATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN MIN 6 MEDAN - Afifah Vinandita; Nani Sri Rezeki; Riris Nurkholidah Rambe; Maulana Arafat Lubis (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
The success of the learning process is seen from the accuracy of the selected learning model so that it can achieve the learning objectives and obtain the learning outcomes optimally. The purpose of the research is to improve learning outcomes in aspects of spiritual attitudes, social attitudes, knowledge, and skills of students by implementing the Problem Based Learning learning model in Civics lessons, the subject matter of Socio-Cultural Diversity of Society. The research subject was students of the class 5-A MIN 6 Medan. The research design uses John Elliot's classroom action research model. They collected data by using tests, observations, and interviews. Data were analyzed descriptively with qualitative and quantitative approaches with the help of STATCAL software. The results of the study proved that in the first cycle, the percentage of student learning outcomes was 17.14% (6 students completed and 29 students had not completed), then increased in the second cycle with a value of 51.42% (18 students completed and 17 students did not complete). ), then increased again in the third cycle with a score of 88.57% (31 students completed and four students did not complete).Keywords: learning outcomes, learning model, PBL, Pancasila and civic education.